Imigração em Angola: um estudo sobre os burundeses na periferia de Luanda - Costa, Beatriz Adão Pascoal da (2023)
The current study is focused into the comprehension on the burundeses Immigration in the Luanda/Angola suburbs. It deals with the trajectory of the citizens' life welcomed as refugees, citizens that don't have many options, they search for inside the African continent, better conditions of life and about the refugees who were taken in by the Angolan government, it constracs itself that the preservation of life was the first rule to take it into account. Frequently persecution victims and, not just this, without protection by side of government originally, the citizens run away from the situation of risk in the countries where they came from and they've subjected in so many cases to precarious conditions of surviving into the host countries. In this situation that involves the nonviolation on the human rights, that in spite of guaranteed, on the practice it doesn't work for these citizens life that demand protection by the government where they are welcomed. Treated majority as a threat by the host governments and in the purpose sense. Being on the asylum way or refuge, they resist and fight constantly longing for a dream of a better life. In this context, we approach the done route until they arrived to the capital; how they live in their everyday life in that city; about the insertion difficulties into the new place; which are the supporting net that they can count on, and from the government side and from non-governmental institutions. We have talked with experts who approached the hard insertion from that part of the population in the country. This research has been accomplished by the use of the oral methodology as privileged resource, to understand the trajectory of life of refugees welcomed by the Angolan government, intending to interpretate the immigration phenomenon as a social factor, focused into our observation. We sought to comprehend the reality of people who subject themselves to immigration, as possibilities of better conditions of life. From the meanings that, by them, they are attributed, about the valorant vocabulary which brings from their origin. When they benefit the oral narrative, we search for conciliating the brought meanings by immigrants to those attributed ones, considering the groups of laws and rules that legitimates the immigration. This way, it uncovered the immigration phenomenon in Angola; their determinants and conditioning; the arrived consequences with the absorption of the populational contingent from others African countries and how this phenomenon takes place meanwhile it demands for the social work in its configuration as occupation. Considering the inclusion of the subject, our concentration has been focused on the Burundeses refugees in Luanda's suburbs, in representation of many refugees and from differents nationalities in Angola